Tinjauan Media Kampanye Visual Dalam Meningkatkan Kesadaran Terhadap Bahaya Penyakit Menular Seksual - Jundy Nisrina Ruhiyat; Rosa Karnita (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2026)
Indonesian adolescents are a group vulnerable to Sexually Transmitted Diseases (STDs) because their increasing curiosity about reproductive health is not accompanied by adequate access to accurate information. Discussions about reproductive health are still considered taboo, causing many adolescents to obtain information from social media and their surrounding environment, where the information is not always reliable. Although visual campaign media have been widely used as educational tools, studies examining visual characteristics that align with adolescents' preferences in Indonesia remain limited. This study aims to identify adolescents' knowledge of STDs and examine the visual characteristics of campaign media as a basis for designing visual campaigns on STDs. The study employed a qualitative descriptive approach with data collected through questionnaires. Data were analyzed using data reduction, data presentation, and conclusion drawing based on two main indicators: knowledge of STDs and preferences for visual campaign media. The participants consisted of junior high school, senior high school, and vocational high school students in Bandung.